O ativismo judicial e decisões transgressoras do garantismo penal no Tribunal de Justiça do Piauí: reflexos teóricos na construção do judiciário decisionista - Batista, Eulane Coelho (2023)
The Judiciary plays a key role in the criminal justice system. However, the way it acts in this branch of law is of particular importance, due to its specific characteristics. Criminal law deals with sensitive issues related to crimes and their respective penalties and punishments, seeking to guarantee security and social order. The judiciary, in turn, is responsible for interpreting and applying criminal laws, ensuring that the rights of the accused are respected throughout the process, in addition to giving effect to the rules for the protection of society against crime. However, some courts adopt activist postures that go beyond the role of the judge, assuming the role of legislator and in criminal matters, using an alleged interpretative opening as a path to unregulated punishment. Thus, the present dissertation has as its object the analysis of decisions of the Court of Justice of Piauí and their compatibility with the Democratic State of Law and the Penal Guarantee linked to it, seeking to understand what influences the position of judges in decisions that go beyond the interpretive limits of the law and offend the rights of the accused. To this end, the following questions are asked. What are the factors that influence judges to act in a certain way, assuming a more proactive posture? Is Judicial activism compatible with the clauses guaranteed in the Democratic State of Criminal Law? Does the attitude of the Court of Justice of Piauí go beyond the limits of the judiciary's activities to the detriment of the rights and guarantees of the accused? The choice of this theme is justified by the importance of investigating activist conduct due to the role played by the Judiciary in democratic societies, when dealing with criminal matters, notably with regard to the guarantees of the fundamental rights of individuals accused of committing crimes. Thus, it will be possible to reflect on the construction of the activist judge and how the theory of law and other factors of a social, political and economic order are privileged for the production of arbitrary decisions. The methodology used in this dissertation will consist of a bibliographic review of primary and secondary sources, such as articles, books, theses and court decisions.